Clinical and Microbiological Characterization of Carbapenem-Resistant Enterobacteriales: A Prospective Cohort Study - Lin, Qiuxia; Wu, Menglu; Yu, Hanbing; Jia, Xiaojiong; Zou, Hua; Ma, Deyu; Niu, Siqiang; Huang, Shifeng (Frontiers in Pharmacology, 2021)
Aim: We aim to depict the clinico-epidemiological and molecular information of carbapenem-resistant Enterobacterales (CRE) in Chongqing，China. Methods: We performed a prospective, observational cohort study, recruiting inpatients diagnosed with CRE infections from 1st June 2018 to 31th December 2019. We did strains identification and molecular characterization of CRE. eBURST analysis was done to assess relationships between the different isolates on the basis of their sequence types (ST), and associated epidemiological data using PHYLOViZ. Clinical parameters were compared between Carbapenemase-producing Enterobacteriales (CPE) and non-CPE group. Findings: 128 unique CRE isolates from 128 patients were collected during the study period: 69 (53.9%) CPE and 59 (46.1%) non-CPE. The majority of CPE isolates were blaKPC-2 (56.5%), followed by blaNDM (39.1%) and blaIMP (5.8%). Klebsiella pneumoniae carbapenemase (KPC)-producing clonal group 11 K pneumoniae was the most common CPE. Antibiotic resistance was more frequent in the CPE group than in the non-CPE group. Independent predictors for CPE infection were ICU admission and hepatobiliary system diseases. Although, there was no significant difference in desirability of outcome ranking (DOOR) outcomes between two groups. At 30 days after index culture, 35 (27.3%, 95% CI 20-35) of these patients had died. Conclusion: CRE infections were related to high mortality and poor outcomes, regardless of CRE subgroups. CPE were associated with prolonged ICU stays and had different clinical and microbiological characteristics than non-CPE.The identification of CPE/non-CPE identification and CRE resistance mechanisms are essential for better guide the clinical administration of patients with CRE infections.